Rigid–flexible coupling dynamics with contact estimator for robot/PTL system. (December 2020) - Zheng, Xiaoliang; Wu, Gongping; Jiang, Wei; Fan, Fei; Zhu, Jiale
In order to enhance sampling efficiency and security when robot maintains power transmission line (PTL), this article develops a new approach for the rigid-flexible coupling dynamics of robot/PTL system, which decouples the large system into two small systems and solves them separately by estimating the contact force. The robot is modelled as a system of rigid bodies by screw theory, while the PTL system is modelled using absolute node coordinate formulation (ANCF). The integration of screw theory, ANCF and contact estimator trained by artificial neural network has not been accomplished before in the literature. The main contribution of this paper is to achieve this integration with the goal of developing a new and general approach for the nonlinear dynamic analysis of the interaction of the rigid maintenance robot with flexible PTL cable. A simplified two-dimensional example is used to compute the effect of the robot/PTL interaction under different operating conditions to have an understanding of the coupling approach between the two systems. A more detailed three-dimensional model was developed, and the results obtained validate the utility and effectiveness of our approach.